Modality and the Evaluative Schema - Mohammad Al-Zahrani (Journal of Umm Al-Qura University for Language Sciences and Literature, 2021)
Linguistic investigations on Hijazi Arabic modal elements have only considered a small class of modals classified under the three domains of modality, and consequently assigned different places in the hierarchy within the Principles and Parameters syntactic approach (P&P) (Chomsky, 1981, 1986) along with insights of Chomsky's Minimalist Program (MP) (Chomsky, 1995, 1999, 2000). The current paper investigates some other HA expressions that evaluate the speaker's attitudes, opinions and judgments from another perspective. It adopts the evaluative schema suggested by Heine (1993) and characterized by the form "it is X to/that Y" where X stands for the evaluative component expressing the speaker's judgement, and Y is the main prediction occurring in the complement selected by X. The purpose of the study is twofold. First, it presents the most common HA expressions that convey the speaker's evaluation towards a proposition using Heine's evaluative schema structure "it is X to/that Y". Second, since Heine's (1993) purpose does not explore the syntax of the evaluative structure, the paper explicates the components of Heine's structure in light of the syntactic studies on HA clauses within the generative syntax theory. The findings show that the evaluative components in the present study belong to different classes occurring in a CP clause. They may be preceded by a realized expletive subject, or by its phonetically null equivalent, and select for CP complements. This work should contribute to the field of HA modality in particular and enhance the discussion of the evaluative schema, in general.